2019
DOI: 10.1016/j.foodchem.2018.10.106
|View full text |Cite
|
Sign up to set email alerts
|

LF 1H NMR T2 relaxation rate as affected by water addition, NaCl and pH in fresh, frozen and cooked minced hake

Abstract: Low-Field Nuclear Magnetic Resonance of proton transverse relaxation signal (T 2 ) was monitored in hake (Merluccius merluccius) mince with different thermal histories (fresh, frozen, cooked) as affected by pH, water and NaCl addition, and it was related to water holding capacity (WHC). Modifications of T 2 signals were found in terms of changes in relaxation times and relative abundance of the relaxation components. The relaxation rate of the major component (1/T 21 ) increased significantly upon frozen stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…But Duflot et al . (2019) found the entrapped water decreased after salting. This could attribute to the higher salt content and different raw material, which led to the water losing from muscle.…”
Section: Resultsmentioning
confidence: 99%
“…But Duflot et al . (2019) found the entrapped water decreased after salting. This could attribute to the higher salt content and different raw material, which led to the water losing from muscle.…”
Section: Resultsmentioning
confidence: 99%
“…the inverse of the relaxation time, depends on exchange processes between water and surfaces which could be considered to be protein molecules in the present study. 29,30 The surface-to-volume ratio determines the relaxation rate and, accordingly, an increase in the distance between the thin and thick filaments is expected to result in an increase in the relaxation time. 29 Therefore, the increase in T 21 relaxation time was caused by a swelling of the myofilament lattice with increasing ionic strength.…”
Section: Water Distribution and Mobility In Mp Gelsmentioning
confidence: 99%
“…In the field of fish products characterization, for example, proton NMR relaxometry has proven to be a powerful technique to provide information on inherent muscle water and water-holding capacity (WHC), which are fundamental parameters in perception during food consumption [ 103 ]. In this regard, it is interesting to highlight the study of Duflot and collaborators [ 104 ] on the monitoring of the Low-Field (LF) 1 H NMR T 2 (proton transverse relaxation signal) relaxation rate in minced hake with different thermal treatments (fresh, frozen, and cooked) taking into account all other parameters that can affect this kind of signal (pH, NaCl, and protein concentration). The authors correlated T 21 (not significantly correlated), T 22 (R 2 = 0.469, significant at p = 0.05) relaxation times, and their corresponding maximum amplitudes A 21 (R 2 = 0.774, significant at p = 0.01) and A 22 (R 2 = 0.760, significant at p = 0.01) with WHC, and they also found that WHC decreased and that the relaxation rate of the major component increased upon frozen storage [ 104 ].…”
Section: Detection Of Frozen–thawed Seafoods By Spectroscopic Techmentioning
confidence: 99%
“…In this regard, it is interesting to highlight the study of Duflot and collaborators [ 104 ] on the monitoring of the Low-Field (LF) 1 H NMR T 2 (proton transverse relaxation signal) relaxation rate in minced hake with different thermal treatments (fresh, frozen, and cooked) taking into account all other parameters that can affect this kind of signal (pH, NaCl, and protein concentration). The authors correlated T 21 (not significantly correlated), T 22 (R 2 = 0.469, significant at p = 0.05) relaxation times, and their corresponding maximum amplitudes A 21 (R 2 = 0.774, significant at p = 0.01) and A 22 (R 2 = 0.760, significant at p = 0.01) with WHC, and they also found that WHC decreased and that the relaxation rate of the major component increased upon frozen storage [ 104 ]. Differently, the study of Shumilina and others is more pertinent to the discrimination between fresh and thawed products.…”
Section: Detection Of Frozen–thawed Seafoods By Spectroscopic Techmentioning
confidence: 99%